2019
DOI: 10.1186/s13104-019-4502-y
|View full text |Cite
|
Sign up to set email alerts
|

Self-care practices and associated factors among adult hypertensive patients in Ayder Comprehensive Specialized Hospital, Tigray, Ethiopia, 2018

Abstract: Objectives To assess self-care practices and associated factors among hypertensive patients in Ayder Comprehensive Specialized Hospital 2017/2018. Result Good self-care practice was found only among 20.3% of respondents. Adherence to not smoking, anti-hypertensive medication, alcohol abstinence, dietary management, physical exercise and weight management was found to be 99.1%, 74.10%, 67.20%, 63.10%, 49.4% and 40.6% respectively. Sex (AOR = 2.254, 95% CI 1.092–4.653), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
55
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(69 citation statements)
references
References 23 publications
11
55
3
Order By: Relevance
“…In this study, Individuals with uncontrolled BP state were 2.141times more likely to practice poor self-care as compared to those who had controlled state of BP. This was in line with a study done at Hiwot Fana and Jugola Hospital Harare, Ethiopia (26) and study done at Ayder hospital (40) this might be due to the fact that good selfcare practice can control blood pressure.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, Individuals with uncontrolled BP state were 2.141times more likely to practice poor self-care as compared to those who had controlled state of BP. This was in line with a study done at Hiwot Fana and Jugola Hospital Harare, Ethiopia (26) and study done at Ayder hospital (40) this might be due to the fact that good selfcare practice can control blood pressure.…”
Section: Discussionsupporting
confidence: 89%
“…What is worse, as many as 40% take no action whatsoever to normalize their BP [ 31 ]. In other studies, the percentage of hypertensive patients with good self-care practices ranged between 20.3 and 37.1% [ 8 , 32 ]. In their study of patients with HT, Gebremichael et al demonstrated an association between good self-care practices and good BP control [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is higher than studies conducted in several parts of Ethiopia; 24% in Debre Berhan, 26 24% in Durame, 39 and 20% in Mekele. 40 This discrepancy could be due to methodological differences. For instance, the study conducted in Durame Town measured the self-care practice using only lifestyle-related items without considering medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…A similar observation was made in a study conducted in Debra Berhan in Ethiopia, 26 but this finding disagrees with the study conducted in Addis Ababa, Ethiopia. 29 This difference is due to the differences in access to media 28,39,40,51 and can have better access to healthcare services than those living in small towns. 25,31,51 In this study, having adequate knowledge about hypertension improves self-care practice.…”
Section: Discussionmentioning
confidence: 99%